GENDER LEADERSHIP: INCLUSIVITY AND A HOLISTIC APPROACH IN PRIVATE UNIVERSITIES GORONTALO - Tety Thalib; Asna Aneta, Zulaecha Ngiu, Juriko Abdussamad (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to analyze the implementation of inclusivity and holistic approaches in higher education in Private Universities (PTS) in Gorontalo, with an emphasis on the role of gender leadership in creating policies that support equality and diversity. Inclusivity in higher education includes providing equal access for all students, while a holistic approach focuses on the development of students as a whole, including academic, social, and character aspects. This study uses a qualitative approach with a case study method, involving in-depth interviews with leaders, lecturers, and students in several PTS in Gorontalo. The results of the study indicate that although a number of PTS in Gorontalo have implemented inclusive policies, there are still challenges related to limited resources and resistance to changes in patriarchal culture that affect gender equality in leadership. In addition, female leadership has been shown to play an important role in encouraging more inclusive policies and empowering female students. This study concludes that in order to achieve inclusive and holistic higher education, collaboration between leaders, lecturers, and students is important in developing policies that strengthen gender equality, as well as increasing women's participation in leadership positions in PTS. These findings are expected to provide recommendations for higher education policies in Gorontalo and Indonesia, especially to encourage gender equality and the development of women's leadership in higher education.